Response System for and Epidemiological Features of COVID-19 in Gyeongsangnam-do Province in South Korea. (16th July 2020) - Wi, Yu Mi; Lim, Su Jin; Kim, Si-Ho; Lim, Seungjin; Lee, Su Jin; Ryu, Byung-Han; Hong, Sun In; Cho, Oh-Hyun; Moon, Kyunglan; Hong, Kyung-Wook; Kim, Sunjoo; Bae, In-Gyu
Abstract: Background: The South Korean government has been combating the coronavirus disease 2019 (COVID-19) outbreak using public information and extensive viral screening. We describe the application of the Korean response system in Gyeongsangnam-do province and outline the epidemiological features of COVID-19 in the cohort. Methods: A Rapid Response Team tracked the patients' activities and identified close contacts. A Patient Management Team made decisions regarding the severity of illness, hospital allocation depending on severity, and time of discharge. A national medical center with 155 beds and 4 university-affiliated hospitals with 48 negative-pressure isolation rooms were dedicated for patients with COVID-19. Results: As of 15 April, 17 400 residents were tested, of whom 111 were confirmed positive cases. Of the 111 patients, 78 were cured and discharged, 2 recovered after mechanical ventilation, and none died. One healthcare worker at the national center tested positive for SARS-CoV-2. All 412 staff members at the center were tested, but there were no additional infections. Cough (30.0%) was the most common initial symptom, whereas anosmia and ageusia were the first symptoms in 14.7% and 15.7% of the patients, respectively. Overall, 25 patients (22.5%) reported having no symptoms at admission and 7 (6.3%) remained asymptomatic at discharge. Conclusions: A response system that enabled the early detection of COVID-19 cases, including asymptomatic and presymptomatic cases, and timely quarantine of these patients and their contacts, along with efficient allocation of medical resources, was the key to curbing the COVID-19 outbreak in Gyeongsangnam-do Province. Abstract : A response system that enabled the early detection of COVID-19 cases, including asymptomatic and presymptomatic cases, and the timely quarantine of these patients and their contacts, was the key to curbing disease transmission in Gyeongsangnam-do Province in South Korea.